Immunization Against Chlamydia trachomatis Polymorphic Membrane Protein D Tetrapeptide Motifs Limits Early Female Reproductive Tract Infection in a Mouse Model - Amanda L. Collar; Andzoa N. Jamus; Julian Flanagan; Susan B. Core; William M. Geisler; Cosette M. Wheeler; Kathryn M. Frietze (Vaccines)
Background/Objectives: Chlamydia trachomatis (Ct) is a common pathogen causing urogenital, anal, oral, and ocular infections. Although extensive vaccine efforts have been underway for decades, there is no licensed vaccine available to prevent human Ct infection. Polymorphic membrane protein D (PmpD) is a highly conserved protein present on the surface of Ct elementary bodies, suggesting an important role Ct biology. Repetitive tetrapeptide motifs GGA(I,L,V) and FxxN are conserved across Pmps and are important for adhesion in the related Chlamydia pneumoniae Pmp21. Methods: Using bioinformatics approaches, we identified amino acids 270 to 294 of PmpD that included two GGA(I,L,V) motifs and an FxxN motif as vaccine targets. Synthetic peptides corresponding to these regions were chemically conjugated separately via the carboxy (C)- or amino (N)-terminus (FxxN 1.1 and FxxN 1.2) to the surface of Qβ virus-like particles (VLPs) and were tested for immunogenicity and protective capacity in mice. Results: Female mice immunized three times with a mixture of Qβ-FxxN 1.1 and Qβ-FxxN 1.2 vaccines without exogenous adjuvant elicited geometric-mean endpoint dilution titers near 104. Further, mice showed decreased infection at early time points when challenged vaginally with luciferase-expressing Chlamydia muridarum over 9 days and a faster time to undetectable infection compared to controls. Immunization with individual vaccines (Qβ-FxxN 1.1 or Qβ-FxxN 1.2) did not show the same degree of reduction. Conclusions: Vaccination against PmpD tetrapeptide motifs is a novel and promising approach for limiting initial Chlamydia infection and warrants further investigation to characterize the mechanism of protection.